2014
DOI: 10.1097/sla.0000000000000955
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Neoadjuvant Chemoradiotherapy on Postoperative Outcomes After Esophageal Cancer Resection

Abstract: Neoadjuvant chemoradiotherapy does not have an impact on the AL rate after EC resection (NCT 01927016).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 31 publications
4
52
2
3
Order By: Relevance
“…Induction therapy may decrease FEV 1 % and D LCO %, thereby increasing the risk of postoperative PCs. However, a recent study [23] did not find an increased rate of PCs in patients who received neoadjuvant chemoradiotherapy compared with those who did not receive neoadjuvant chemoradiotherapy. Therefore, exclusion of patients who received induction may not influence the result of this study.…”
Section: Discussionmentioning
confidence: 94%
“…Induction therapy may decrease FEV 1 % and D LCO %, thereby increasing the risk of postoperative PCs. However, a recent study [23] did not find an increased rate of PCs in patients who received neoadjuvant chemoradiotherapy compared with those who did not receive neoadjuvant chemoradiotherapy. Therefore, exclusion of patients who received induction may not influence the result of this study.…”
Section: Discussionmentioning
confidence: 94%
“…What was notable was that all of the six patients with leakage had undergone NCRT and cervical anastomosis. Some studies suggested that NCRT was a risk factor for morbidities and mortalities (19,20), while some others hold the opposed idea (21)(22)(23). A retrospective study from our center reported that cervical leakage occurred more frequently than intrathoracic leakage (23.6%, 145/615 vs. 5.0%, 101/2,023, P<0.001) (24).…”
Section: Discussionmentioning
confidence: 99%
“…En considérant que la moitié des patients sera atteinte d'une rechute locale dans le volume traité et qu'un tiers d'une évolution métastatique, il nous semble que l'irradiation ganglionnaire prophylactique doit être mesurée, étant donné la faible fréquence des rechutes ganglionnaires isolées hors volume irradié. Il est intéressant de rappeler ici que, malgré le fait que les séries chirurgicales mettent en évi-dence un tiers d'atteintes ganglionnaires du haut médiastin ou cervicales lors de curages étendus, les rechutes ganglionnaires susclaviculaires après chirurgie sont jugées suffisamment rares pour que le curage cervical ne soit plus utilisé par la plupart des équipes chirurgicales [29,30]. En effet, étant donné le peu de rechutes ganglionnaires cervicales et la morbidité associée au curage cervical, celui-ci n'est plus recommandé.…”
Section: Approche Empiriqueunclassified